Publication Opportunities of Non-research Articles in Health - Joel Rey Ugsang ACOB; Heru Santoso Wahito Nugroho; Tanko Titus Auta (Health Notions, 2021)
The pandemic may isolate researchers, but is not ceasing the desire to generate newer concepts as effective material to publish. This manuscript epitomizes non-research articles in health which are promising to sustain the generation of ideas and knowledge in the absence of the conventional research process through outdoor surveys.Keywords: publication; health; non research article